Age determination, stable carbon, and hydrogen isotope composition of n-alkanes from Mfabeni peatland - Miller, Charlotte; Finch, Jemma M; Hill, Trevor; Peterse, Francien; Humphries, Marc; Zabel, Matthias; Schefuß, Enno (PANGAEA, 2019)
The scarcity of continuous, terrestrial, palaeoenvironmental records in eastern South Africa leaves the evolution of late Quaternary climate and its driving mechanisms uncertain. Here we use a ∼7 m long core from Mfabeni peatland (KwaZulu-Natal, South Africa) to reconstruct climate variability for the last 32 000 years (cal ka BP). We infer past vegetation and hydrological variability using stable carbon (δ13Cwax) and hydrogen isotopes (δDwax) of plant-wax n-alkanes and use Paq to reconstruct water table changes. Our results indicate that late Quaternary climate in eastern South Africa did not respond directly to orbital forcing or to changes in sea-surface temperatures (SSTs) in the western Indian Ocean. We attribute the arid conditions evidenced at Mfabeni during the Last Glacial Maximum (LGM) to low SSTs and an equatorward displacement of (i) the Southern Hemisphere westerlies, (ii) the subtropical high-pressure cell, and (iii) the South Indian Ocean Convergence Zone (SIOCZ), which we infer was linked to increased Antarctic sea-ice extent. The northerly location of the high-pressure cell and the SIOCZ inhibited moisture advection inland and pushed the rain-bearing cloud band north of Mfabeni, respectively. The increased humidity at Mfabeni between 19 and 14 cal kyr BP likely resulted from a southward retreat of the westerlies, the high-pressure cell, and the SIOCZ, consistent with a decrease in Antarctic sea-ice extent. Between 14 and 5 cal kyr BP, when the westerlies, the high-pressure cell, and the SIOCZ were in their southernmost position, local insolation became the dominant control, leading to stronger atmospheric convection and an enhanced tropical easterly monsoon. Generally drier conditions persisted during the past ca. 5 cal ka BP, probably resulting from an equatorward return of the westerlies, the high-pressure cell, and the SIOCZ. Higher SSTs and heightened El Niño–Southern Oscillation (ENSO) activity may have played a role in enhancing climatic variability during the past ca. 5 cal ka BP. Our findings highlight the influence of the latitudinal position of the westerlies, the high-pressure cell, and the SIOCZ in driving climatological and environmental changes in eastern South Africa.